0242 Consumption of the Long-Chain Fatty Acid Docosahexaenoic Acid In Relation To Sleep Timing And Duration In Adolescents: An Actigraphy-based Study In Mexico City. (12th April 2019) - Jansen, Erica C; Conroy, Deirdre A; Burgess, Helen J; Louise, O'Brien; Cantoral, Alejandra; Tellez Rojo, Martha Maria; Peterson, Karen E; Baylin, Ana
Abstract: Introduction: Delayed sleep timing and short sleep duration represent a significant public health burden in adolescent populations. Some substances obtained through diet (such as caffeine) are known to affect sleep, yet other dietary components that could alter sleep in adolescents are unclear. We investigated whether plasma levels of docosahexaenoic acid (DHA), a long-chain fatty acid that can be obtained through diet (e.g. from fatty fish such as tuna), were related to sleep timing and duration in adolescents. Methods: The study population included 405 Mexico City adolescents (average age (SD)= 14.2 (2.1) years; 48% males) who took part in a 2015-2016 follow-up visit as a part of an ongoing cohort study. Fatty acid levels were measured in plasma, as percentage of total fatty acids. Sleep midpoint and duration were assessed with 7-day actigraphy immediately following the fatty acid blood draw. DHA plasma levels we categorized into quartiles (Q1-Q4; Q4=highest fatty acids). Linear regression was conducted with sleep characteristics as separate outcomes and quartiles of DHA as the exposure, adjusting for sex, age, caffeine, total energy intake, and BMI-for-age Z scores. Results: Mean (SD) plasma DHA was 1.2 (0.4) %. In adjusted analysis, plasma DHA was positively and linearly associated with sleep duration on the weekends (e.g. those in Q4 compared to Q1 had 31 minutes longer duration [95% CI 6 to 56], P, trend=0.006). Higher DHA also associated with earlier sleep timing during both weekdays and weekends, although in a non-linear fashion (largest difference was a 0.78-hour later weekday midpoint in Q2 compared to Q4 [0.35 to 1.12]). Conclusion: Plasma levels of DHA, which reflect typical dietary intake, were associated with earlier sleep timing and longer weekend sleep duration in Mexican adolescents. Whether dietary interventions or DHA supplementation could improve sleep in adolescent populations deserves consideration in randomized trials. Support (If Any): Dr. Jansen is supported by the NIH/NHLBI grant 5T32HL110952-05. The project was also supported by a UM Momentum Center Pilot and Feasibility grant.